2021
DOI: 10.1007/s10552-021-01429-x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to pesticides and central nervous system tumors: results from the CERENAT case–control study

Abstract: Background:The etiology of the central nervous system (CNS) tumors remains largely unknown. The role of pesticide exposure has been suggested by several epidemiological studies, but with no de nitive conclusion. Objective: To analyze associations between occupational pesticide exposure and primary CNS tumors in adults in the CERENAT study. Methods: CERENAT is a multicenter case-control study conducted in France in [2004][2005][2006]. Data about occupational pesticide uses -in and outside agriculturewere collec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 31 publications
(37 reference statements)
5
11
0
Order By: Relevance
“…11 Another study reported a decreased risk in French viticulture for harvesting (OR = 0.50 [0.32-0.76]) but an elevated risk for long pesticide exposures. 10 Our results are closer to those of AGRICAN, with a positive trend observed in viticulture.…”
Section: Gliomasupporting
confidence: 84%
See 1 more Smart Citation
“…11 Another study reported a decreased risk in French viticulture for harvesting (OR = 0.50 [0.32-0.76]) but an elevated risk for long pesticide exposures. 10 Our results are closer to those of AGRICAN, with a positive trend observed in viticulture.…”
Section: Gliomasupporting
confidence: 84%
“…Other French studies are also limited both geographically and in scope, and pertained only to a small proportion of the agricultural workforce. [10][11][12] It is therefore paramount to consolidate existing and recent evidences by studying the entire French agricultural workforce on the whole metropolitan territory.…”
Section: Introductionmentioning
confidence: 99%
“…Dividing farms by crop type, animal type, and potential for exposure to pesticides revealed that pesticides significantly impacted risk for brain cancer [ 98 ]. A study in France found that agricultural workers overall did not have higher rates of brain cancer, but that working in agriculture for over 10 years and pesticide exposure were strongly associated with brain cancer suggesting that pesticide exposure and not agricultural work itself may be the main risk factor [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies that did seek further information about job subtype often found differences between job subtypes [ 55 , 61 , 65 , 99 ]. Estimating time spent in the agricultural occupation is another important consideration [ 97 ]. Multiple studies found that the number of years spent in the profession moderated the relationship between agricultural work and brain health, possibly enhanced by exposure to pesticides [ 97 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation